Mindfulness, movement control, and attentional focus strategies: effects of mindfulness on a postural balance task - Kee, Y.; Chatzisarantis, Nikos; Kong, P.; Chow, J.; Chen, L. (Human Kinetics, 2012)
We examined whether the momentary induction of state mindfulness benefited subsequent balance performance, taking into consideration the effects of dispositional mindfulness. We also tested whether our mindfulness induction, grounded in sustaining moment-to-moment attention, influenced the attentional focus strategies that were adopted by the participants during the balancing task. Balance performance was ascertained based on approximate entropy (ApEn) of the center of pressure (COP) data. The study involved 32 males (age: M = 22.8, SD = 1.94) who were randomly assigned to the mindfulness or control group. Using difference in pretest to posttest performance based on the medio-lateral movements as the dependent variable, the test for interaction showed that the mindfulness induction was more effective for participants with higher dispositional mindfulness. Participants who underwent mindfulness induction also reported greater use of external focus strategies than those in the control group. Results suggest that momentary mindful attention could benefit balance performance and affect the use of attentional focus strategies during movement control.